IMPLEMENTASI PROSES PERIZINAN DAN PENGENDALIAN PEMANFAATAN RUANG MELALUI IZIN MENDIRIKAN BANGUNAN (IMB) DIKECAMATAN TIRAWUTA KABUPATEN KOLAKA TIMUR - Ilham, Ilham; Rianse, Usman; Yunusi, Lukman (Aksara Public, 2019)
This study aims to determine and analyze; Implementation of procedures for the process of controlling spatial use through IMB; Conformity of building spatial planning (RDTR) policy towards IMB implementation; Factors that cause the suitability or incompatibility of spatial use through IMB to the spatial plan (RDTR); and Directions for the use of space in an effort to control spatial use through IMB in Tirawuta District. This type of research uses a qualitative approach to survey design. Regional samples are determined by census sampling, community samples are determined by sampling quota. Data were analyzed by descriptive qualitative and spatial analysis through a map overlay process. The results of the study concluded that the implementation of building management procedures through the issuance of IMB in controlling spatial use had been running "effectively" and the implementation of the process / provisions was "very effective". The building utilization activities through the IMB instrument against RDTR are appropriate or considered "quality" (81.82% conformity). Factors causing incompatibility are; land ownership (95.78%); The building location is not in accordance with the spatial pattern (4.22%); The area of ​​the building floor is partially found above 100 m2; (10.24%); The floor of the house is more than one floor (5.42%); Buildings are not in accordance with the distance with the border of the road (22.29%); and Buildings that are not in accordance with river / lake border (4.82%). Directions for the use of space in an effort to control the use of space through IMB instruments in the RDTR are; a) Directions for procedures and processes are; the application of sanctions for mismatches in spatial use; implementing a Building Management Information System (SIMBG); forming a Building Expert Team (TABG) and building inspector; enforce Building Worthy Certificate (SLF) of buildings; the need for policies (at the level of Regional Regulation) RTB; implementation of "temporary IMB"; b) Direction for spatial incompatibility is to carry out further studies of discrepancies; Increasing IMB socialization activities and conducting assessments; periodic space use evaluation; provide written warning (administrative sanctions) for inappropriate building owners.